La disfunción familiar y pensamientos suicidas en un adolescente de 13 años de la ciudad de Cayambe - Benavides Molina, Nancy Elena (2022)
The work carried out focuses on the analysis of a case in the area of clinical psychology focused on the dysfunctional family, causes, consequences and a series of unknowns that are unknown to this thematic employee. Each situation occurs from a dysfunctional family and how this event has a negative impact on someone who is going through the stage of adolescence. Stage in which a series of significant changes occurs, such as; psychological, emotional and physical. Due to the series of volatility of changes, this being the reason to turn an adolescent into a much more vulnerable and intolerant person to any situation that arises, becoming a stage of formation of the personality of an individual. Associating dysfunctionality as negative to affect thoughts of suicide in adolescents who are going through this type of situation. Suicidal thoughts occur because there is no approval from anyone and the only thing they observe are conflicts and a circumstance that has no way out, seeing suicide as a solution to the event presented at that time.